The Potential Roles of Exosomal Non-Coding RNAs in Hepatocellular Carcinoma - Wang, Wei; Hao, Li-Ping; Song, Haizhu; Chu, Xiao-Yuan; Wang, Rui (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the sixth highest-incidence cancer and the 4th most deadly cancer all over the world, with a high fatality and low diagnostic rate.Nowadays, Excessive alcohol consumption, type-2 diabetes ,smoking and obesity have become some primary risk factors of HCC. As intercellular messenger transporting information cargoes between cells,Exosomes are extracelluar nanovesicles released by most types of cells including tumor cells and non-tumor cells and play a pivotal role in establishing an HCC microenvironment.They are composed of messenger RNA (mRNA), non-coding RNAs (ncRNAs) , proteins, lipids and transcription factors. The three main ncRNAs in exosomes are microRNA (miRNA), long non-coding RNA (lncRNA), circular RNA (circRNA). NcRNAs , identified as essential components,are selectively sorted into exosomes and exosomal ncRNAs show great potential in regulating tumor development, including proliferation, invasion,angiogenesis, metastasis, immune escape and drug resistance.Here, we chiefly review the formation and uptake of exosomes,classification of exosomal NcRNAs and current research on the roles of exosomal ncRNAs in HCC progression We also explored their clinical applications as new diagnostic biomarkers and therapeutic avenues in HCC.